'Non per instituir altri'? Attitudes to Rule-Following in Sixteenth-Century Poetics. (9th June 2021) - Hetherington, Michael
Abstract: Literary historians tend to associate a poetics of rule-following with seventeenth-century neoclassicism, and with the sixteenth-century Italian commentators and theorists on whom the neoclassical critics drew; but thinking about the value and limitations of rules for writing is a pervasive and philosophically distinctive feature of pre-modern poetics more generally. Drawing on texts from different national literatures, on the literary theory of classical antiquity, on reflections on rule-following in non-literary early modern disciplines, and on some of the rich thinking on rules by modern philosophers, this article attempts to identify and describe some of the distinct kinds of rule-making and rule-following that constituted the discipline and practice of poetics in the sixteenth-century. To do so it focuses on three texts: Jodocus Badius Ascensius' edition of Horace's Ars poetica (1503), which divides the text up into 'regulae'; Julius Caesar Scaliger's Poetices libri septem (1561), which probes the ways in which ancient texts might function as 'normae' to which literary practice might be referred; and Samuel Daniels' Musophilus (1599), which deeply if idiosyncratically meditates on the poet's obligations and freedoms, and voices a profound scepticism about a literary practice that conforms to rules inherited from prior writers or imposed by critics.